2010
DOI: 10.3109/00365591003636596
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a cranberry (Vaccinium macrocarpon) preparation in reducing asymptomatic bacteriuria in patients with an ileal enterocystoplasty

Abstract: Treatment with a cranberry compound seems to be effective in reducing asymptomatic bacteriuria in patients with an ileal enterocystoplasty. These results need to be validated by further double-blind randomized studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 17 publications
(16 reference statements)
1
13
0
Order By: Relevance
“…This bacteriuria has been independantly studied by our department. A new preventive approach using a cranberry (Vaccinium macrocarpon) preparation has been efficient in our patients for reducing this bacteriuria [33].…”
Section: Discussionmentioning
confidence: 99%
“…This bacteriuria has been independantly studied by our department. A new preventive approach using a cranberry (Vaccinium macrocarpon) preparation has been efficient in our patients for reducing this bacteriuria [33].…”
Section: Discussionmentioning
confidence: 99%
“…The comments received indicated that the applicant did not agree with the conclusion of the Panel that the results of the study by Botto and Neuzillet (2010) obtained in a population of patients after radical cystectomy and ileal cystoplasty cannot be extrapolated to the target population (i.e. general population) for this claim.…”
Section: Comments Related To the Panel's Assessment Of The Study By Bmentioning
confidence: 97%
“…The literature reveals that the consumption of cranberry (Vaccinium macrocarpon) juice helps prevent UTI [6][7][8][9][10][11]; it has been used by Native Americans for more than 200 years [12]. Several theories regarding the effect of cranberry juice have been proposed by different studies [6].…”
Section: Introductionmentioning
confidence: 99%
“…Another compound-proanthocyanidin-identified in the cranberry juice is found responsible and considered to be the main active ingredient for inhibiting P-fimbriated E. coli adherence to uroepithelial cells [8]. The inhibition of adherence activity of this compound has been observed not only to sensitive but also for trimethoprim-sulfamethoxazoleresistant uropathogens [9] and to asymptomatic bacteriuria in patients with an ileal enterocystoplasty [11]. Furthermore, it has not been evaluated and investigated with multi-drug resistant uropathogens, which remains unexplored to date.…”
Section: Introductionmentioning
confidence: 99%